REVIVING KNOWLEDGE ON EQUIPMENT FAILURES AND IMPROVING RISK MANAGEMENT AT INDUSTRIAL SITES - Bragatto, Paolo; Agnelo, Patrizia; Ansaldi, Silvia; Artenio, Emanuele; Delle Site, Corrado (Journal of Applied Engineering Science, 2015)
The knowledge about pressure equipment failure modes and rates is essential for the risk management. In the Seventies an incomparable effort was made by National Authorities, which at that time  controlled the pressure equipment, aiming at providing the industry with trustable reliability parameters, which are still in us, even though repeatedly amended by experts.  In order to revive and update the knowledge on this matter, the judgment of the experts is not enough and much more data on the field must be gathered. Experimental studies on a large scale are now impossible, thus the only way is to exploit potential of semantic search and the huge data in the public domain. The information scattered in the web, tied together, may provide industry and authorities with the knowledge they need to make the right decisions.
Keywords: Semantic search; Failure modes; Pressure equipment